(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background: College students typically experience back pain, which is frequently caused by extended sitting and bad posture. Inappropriate seating arrangements, prolonged study sessions, and electronic device use all contribute to musculoskeletal pain. This study highlights the need of awareness and preventive measures by examining the relationship between sitting position and back pain. Objective: The purpose of this study is to look into the relationship between college students’ back pain and their sitting position. It examines for typical postural behaviors, evaluates how they affect spinal health, and identifies risk factors for back pain. The study also aims to raise awareness and provide preventative measures to enhance students’ posture and reduce their discomfort. Method: This study explores the link between college students’ back pain and sitting posture through a cross-sectional survey and observation. Data is collected using questionnaires on sitting habits and self-reported pain. Posture assessments identify common postural changes. Statistical analysis is used to find correlations between posture and back pain. Result: The study identified a strong connection between poor sitting posture and back pain in Karachi college students. NMQ and VAS data showed a high prevalence of lower back pain in both short- and long-term durations. Correlation analysis linked specific pain regions to poor posture. Chi-square tests confirmed statistical significance by rejecting null hypotheses. Diagnostic assessments supported the reliability and accuracy of the findings. Conclusion: The research finds that bad sitting posture is a major cause of low back pain in Karachi’s college students, especially in younger and female students. Prolonged sitting during academic tasks is frequently linked to lower back and neck pain, according to NMQ and VAS data. These findings emphasize the biomechanical effects of bad posture on spinal health and stress the critical necessity to encourage preventive techniques, posture education, and ergonomic awareness in schools.